Phenomena and Computational Models of Non-Proportional Fatigue of Materials - Skibicki, Dariusz (SpringerBriefs in Computational Mechanics, 2014)
This book gives an overview on the fatigue of materials under non-proportional loads. It presents the rich spectrum of phenomena and treats various computational models to mathematically describe the non-proportional fatigue of materials.